The Relationship of Muslimah Clothing with The Morals of Santriwati at House of an Islamic Boarding School Hasanatul Barokah, Tambusai District, Rokan Hulu Regency - Hamzah Hamzah; Siti Aisyah Nasution (Yayasan Riset dan Pengembangan Intelektual, 2022)
Muslimah clothing is clothing that is in accordance with the provisions set by Islamic law, and the wearer reflects a Muslim woman who is obedient to the teachings of her religion in dress procedures. Morals are characteristics that are inherent in a person and become his identity. In addition, morality can also be interpreted as a trait that has been accustomed, inculcated, ingrained, so that it becomes a habit and is easy to implement. The formulation of the problem in this study is how the relationship between Muslim women's clothing and the morals of female students is. The purpose of the study was to determine a significant relationship between Muslim women's clothing and the morals of santriwati. The type of correlational research, with a population of 127, and a sample of 32 people, data collection techniques with questionnaires and documentation, formulation based on the results of data processing and analysis that the author did, then obtained the conclusion that there is a significant relationship between Muslim clothing and the morals of the students of the Hasanatul Barokah Islamic Boarding School, Tambusai sub-district, Rokan Hulu Regency. santriwati's morals is 0.75, according to the interpretation of the correlation coefficient the value of 0.75 lies in the 0.60-0.799 interval with the criteria of a strong relationship level